Facile Spray‐Pyrolysis Synthesis of Yolk–Shell Earth‐Abundant Elemental Nickel–Iron‐Based Nanohybrid Electrocatalysts for Full Water Splitting. Issue 23 (7th November 2017) - Li, Hao; Ci, Suqin; Zhang, Mengtian; Chen, Junxiang; Lai, Keyuan; Wen, Zhenhai
Abstract: The development of high‐activity electrocatalysts for water splitting that comprise only inexpensive, earth‐abundant elements is critical but remains a daunting challenge. In this work, yolk–shell Ni3 Fe/Ni3 FeN was prepared by a spray‐pyrolysis technique, which could be scaleable. The yolk–shell Ni3 Fe/Ni3 FeN presents excellent catalytic activity for the oxygen evolution reaction (OER) and the hydrogen evolution reaction (HER) with overpotentials of 268 and 166 mV at 10 mA cm −2, respectively, and bears a prominent electrochemical durability. Overall water splitting with an electrolyzer containing the yolk–shell Ni3 Fe/Ni3 FeN as the cathode and anode only requires a cell voltage of 1.62 V to reach a current density of 10 mA cm −2 . The present research not only introduces a new route for the synthesis of advanced functional electrocatalysts for overall water splitting but also sheds light on their potential commercial applications. Abstract : Hard boiled : Yolk–shell Ni3 Fe/Ni3 FeN nanohybrids are prepared through spray pyrolysis followed by nitridation treatment; the nanohybrids show favorable activity as bifunctional electrocatalysts for the hydrogen reduction reaction and the oxygen evolution reaction. A homemade electrolyzer requires an applied voltage of only 1.62 V to achieve a current density of 10 mA cm −2 for water splitting.